2016
DOI: 10.1111/hsc.12399
|View full text |Cite
|
Sign up to set email alerts
|

Access to therapy services for people with disability in rural Australia: a carers’ perspective

Abstract: In Australia and around the world, people with disability and their carers living in rural areas face additional challenges compared to their urban-dwelling counterparts. This cross-sectional study explored current access to therapy services for people with disability living in western New South Wales as reported by their primary carers. Data were collected using an online and paper survey distributed to carers, from December 2012 until June 2013. Information was sought about the carers, the person they care f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 18 publications
3
38
1
2
Order By: Relevance
“…This current study did not go into depth about location of new graduate employment, but it does provide evidence that over one‐third may return home and what factors may influence such decisions. With the reported shortage and difficulties in accessing specialist services in rural and regional areas, including occupational therapy (Gallego et al ., ; McKinstry & Cusick, ) the findings of this research can assist those tackling this important issue. Specifically, targeting potential students from regions with limited services in which the profession and health agencies can provide additional support is worth investigation as a way to improve this situation.…”
Section: Discussionmentioning
confidence: 81%
“…This current study did not go into depth about location of new graduate employment, but it does provide evidence that over one‐third may return home and what factors may influence such decisions. With the reported shortage and difficulties in accessing specialist services in rural and regional areas, including occupational therapy (Gallego et al ., ; McKinstry & Cusick, ) the findings of this research can assist those tackling this important issue. Specifically, targeting potential students from regions with limited services in which the profession and health agencies can provide additional support is worth investigation as a way to improve this situation.…”
Section: Discussionmentioning
confidence: 81%
“…However, the moderating role of disabilities has been investigated in very few studies. These have shown that on one hand rural living can impact negatively on health because of geographical isolation and limited accessibility to resources (18,19), but on the other hand, an overcrowded urban environment presents stressors and barriers (e.g., noisy traffic) that can cause withdrawal from outdoor activities (20,21). In line M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 NEIGHBOURHOOD URBANITY, DISABILITIES, AND COGNITIVE HEALTH IN AGEING with these studies, investigations looking at the proximal environment of residence suggest a nonlinear association between neighbourhood urbanity and cognitive outcomes in older age, for instance in terms of residential density (22), or land-use mix (23).…”
Section: Introductionmentioning
confidence: 99%
“…Das Vorhandensein von Barrieren im Gesundheitswesen kann sich negativ auf die Inanspruchnahme von Gesundheitsleistungen auswirken, weshalb ein gleichberechtigter Zugang zum Gesundheitswesen ohne Barrieren elementar für eine bedarfsgerechte Gesundheitsversorgung ohne Diskriminierung ist [5,22,29]. Im zweiten Nationalen Aktionsplan der Bundesregierung zur Umsetzung der UN-BRK wurde deshalb ein Handlungsschwerpunkt auf die "Bedarfsgerechte Ausgestaltung der Gesundheitsversorgung und Pflege für Menschen mit Behinderung" gelegt [7].…”
Section: Inanspruchnahme Und Wahrgenommene Barrieren Des Gesundheitswunclassified
“…Bezüglich der Inanspruchnahme von psychologischen Fachärzt*innen werden die aufgezeigten Ergebnisse durch nationale Studien bestätigt, welche sich allerdings nur auf Menschen mit geistiger Behinderung beziehen [8,24]. Aus internationalen Studien wird ersichtlich, dass Menschen mit Behinderung häufiger eine psychologische Gesundheitsversorgung erhalten als Menschen ohne Behinderung [7,26]. Dies könnte bspw.…”
Section: Introductionunclassified